The Value of a Healthy Home: Lead Paint Remediation and Housing Values - Stephen B. Billings; Kevin T. Schnepel (Institute of Labor Economics (IZA), 2017)
The presence of lead paint significantly impairs cognitive and behavioral development, yet little is known about the value to households of avoiding this residence-specific environmental health risk. In this paper, we estimate the benefits of lead-paint remediation on housing prices. Using data on all homes that applied to a HUD-funded program in Charlotte, North Carolina, we adopt a difference-in-differences estimator that compares values among remediated properties with those for which an inspection does not identify a lead paint hazard. Results indicate large returns for public and private investment in remediation with each 1 spent on lead remediation generating 2.60 in benefits as well as a reduction in residential turnover.
Keywords: Q51; Q52; Q58; R21; R23; R31; I18; 330; lead paint exposure; lead hazard remediation; value of environmental health risk; urban environmental health